Співробітництво миротворчих місій Організації Об’єднаннях Націй: участь України - Лук’янов, О.Л. (Альманах права, 2012)
Стаття висвітлює питання співпраці миротворчих місій Організації Об’єднаних Націй. Автор розглядає питання участі у ній України з точки зору вітчизнаної нормативно-правової бази. Запропоновано варіанти підвищення ефективності міжмісійної взаємодії, відповідних змін до законодавства України, дій України при обговоренні питань міжмісійного співробітництва в рамках ООН. Зроблено висновок про перпективність подальших досліджень у цій сфері. Статья освещает вопросы сотрудничества миротворческих миссий Организации Объединенных Наций. Автор рассматривает вопрос участия в ней Украины с точки зрения отечественной нормативно-правовой базы. Предложены варианты повышения эффективности межмиссионного взаимодействия, соответствующих изменений в законодательство Украины, действий Украины при обсуждении вопросов межмиссионного сотрудничества в рамках ООН. Сделан вывод о перспективности дальнейших исследований в данной сфере. This article examines certain aspects of Ukrainian participation in inter-mission cooperation of peacekeeping missions. This topic is particularly essential for Ukraine because Ukrainian peacekeepers from 56th Separate Helicopter Detachment played important role in one of the most recent examples of such cooperation in C ôte d’Ivoire and saw action during this deployment. In Ukraine this topic has not been subject to significant legal research. Abroad it was studied by, for example, Victor Angelo in Inter-mission cooperation Reflecting on Sudan and Central Africa Experiences. The goal of the article is to examine national legal mechanisms of participation of Ukrainian peacekeepers in inter-mission cooperation. The article starts with a brief introduction into international developments in this area (limited resources of United Nations, report of the Secretary General on inter-mission cooperation, situation in C ô te d’Ivoire) and then examines Ukrainian experience in inter-mission cooperation mostly from national point of view and in conjunction with national legislation. It follows a chain of laws, presidential decrees and resolutions of government which formalized the decision to redeploy Ukrainian troops from United Nations Mission in Liberia (UNMIL) to United Nations Operation in C ô te d’Ivoire (UNOCI). Ukrainian troops were already deployed to Liberia and a decision to provide support to UNOCI had to go through the same process as any other decision to participate in a peacekeeping operation — it was taken by President signing his decree and then affirmed by Parliament voting for respective law. The only difference it that troops were deployed from the neighboring mission and not from Ukraine itself. There were several interesting issues. For example, at first parliament authorized Ukrainian presence in C ô te ’Ivoire for three month while United Nations Security Council resolution 1967 (2011) extended their mandate only for four weeks. Ukrainian Parliament also adopted special resolution making two important recommendations to Cabinet of Ministers: (1) to make sure that Ukrainian unit in Côte d’Ivoire will be manned solely on voluntary basis and (2) to increase pay of personnel deployed to this mission in 2,5 times. Both recommendations were taken into account and deserve to be applied if this practice is continued. Yet the most important question is whether this practice should be continued. Positive answer to this question would warrant respective changes to guiding documents — from capstone documents that define the very framework of Ukraine’s participation in peace operations to manuals that describe participation in lower levels. If Ukraine supports inter-mission cooperation it makes sense to use Ukrainian voice and vote in United Nations institutions to promote this idea. One has to be ready to accept an invitation to more active participation in inter mission cooperation than. While making changes to national legislation Ukraine will also need to augment these measures by undertaking steps to foster further discussion and normative regulation of this matter in international level, particularly removing disagreements between these two levels. Ukraine shall also display caution while deciding whether to participate in operations that is likely to use force (like in Cô te d’Ivoire). As the topic of inter-mission cooperation is extremely broad, any of its elements merits separate and detailed research. This form of international cooperation is fairly effective right now, in a given region at a given time. It will probably generate enough empiric material for a proper analysis.